Results of Achieve the Effectiveness of Regional Revenue Agency in Local Tax Services in Barru District - Dewi Utari; Gita Susanti; Badu Ahmad (Enrichment : Journal of Management, 2021)
The midst of the many needs for regional financing and the complexity of the needs of the citizens, of course, the regional government must be able to explore its own financial sources as an autonomous region so that the implementation of government functions can run effectively and efficiently, namely in the field of government and services to the community. In indonesia itself over the last few years, tax revenue has increased significantly, both in nominal and as a percentage of the total state revenue. On the other hand, in general, the percentage of taxpayers is still very small compared to the total population in Indonesia In this study, the author uses scott's theory. In analyzing the effectiveness of regional revenue agency in local tax services in barru district, "there is a demand to achieve the effectiveness of tax services which the researcher divides into three variables outcomes, process, and structure and on this topic the researcher will describe the achievement of the effectiveness results of the regional revenue agency in service delivery. Local taxes in the district of barru the above theory is used as a tool to analyze the problems that exist in this study. Based on the results of the study that the process of paying taxes in the district of barru is also fairly convoluted so that it is a factor in people's laziness in paying taxes, in fact an integration of the tax payment system has been carried out within the scope of bappeda but there are many obstacles such as the lack of human resources in this program and knowledge on the ongoing basis of the ease of paying taxes through applications, bappeda is also expected to be productive in innovating, for example collaborating with banks in order to facilitate tax services, because pbb taxes are now available through the application, they do not have to come directly.